The Influence of Investment Knowledge, Motivation, And Income on Investment Decisions Shariah Mutual in The Community Pekanbaru City - Khairul Fadilah; Mahyarni; Syahpawi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of investment knowledge, motivation, and income on investment decisions in sharia mutual funds among the people of Pekanbaru City. The primary background for selecting this location is the high economic potential and the dominance of the productive-age population in Pekanbaru. This research employs a quantitative method, with data collection conducted through questionnaires distributed to 100 respondents in Pekanbaru City. Data analysis techniques include multiple linear regression analysis using SPSS 26 software, encompassing research instrument tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis. The results indicate that the t-count for investment knowledge is 1.267 < 1.984 (t-table) with a significance value of 0.208 > 0.05, suggesting that investment knowledge has no significant influence on sharia mutual fund investment decisions among the people of Pekanbaru City. Conversely, the t-count for motivation and income are 4.520 and 4.418, respectively, both exceeding the t-table value of 1.984, with significance values less than 0.05 (0.000 < 0.05). This indicates that motivation and income have a positive and significant influence on sharia mutual fund investment decisions. Furthermore, the F-count (158.874 > 2.70) confirms that investment knowledge, motivation, and income simultaneously have a significant effect on investment decisions. The coefficient of determination (R2) of 0.827 shows that these three variables explain 82.7% of the variation in investment decisions, while the remaining 17.3% is explained by other variables outside this research model.